2006
DOI: 10.1002/j.2161-0045.2006.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Career Competencies for Career Success

Abstract: This article addresses the general question as to which competencies employees need to possess in order to engage in self-management in their career development.The authors distinguished and operationalized 6 career factors and competencies of self-management in career development. A quantitative study was performed using 1,579 employees in 16 Dutch companies to investigate the relationship between career competencies and career success. The results indicate that, among others, the factors career control and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 24 publications
4
94
1
6
Order By: Relevance
“…Employers could, for example, make better use of the media to attract black students, because this ethnic group regards 'information obtained from the media' as a more important influencing factor in career choice than do white students. Both higher education institutions and industry can help students to take greater responsibility for their career goals and planning, as today's students have to educate and market themselves continually to thrive in the fiercely competitive job environment (Kuijpers et al, 2006). Higher education institutions could consider graduate career portals for their alumni to help industry to locate experienced talent (Mnqeta, 2008).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Employers could, for example, make better use of the media to attract black students, because this ethnic group regards 'information obtained from the media' as a more important influencing factor in career choice than do white students. Both higher education institutions and industry can help students to take greater responsibility for their career goals and planning, as today's students have to educate and market themselves continually to thrive in the fiercely competitive job environment (Kuijpers et al, 2006). Higher education institutions could consider graduate career portals for their alumni to help industry to locate experienced talent (Mnqeta, 2008).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The elements of self-guidance such as personal initiative, preparedness of change and career competencies are related to career success (Kuijpers et al, 2006). Personality is related to career success (Guthrie et al, 1998;Ballout, 2007;Wolff and Kim, 2012).…”
Section: Careermentioning
confidence: 99%
“…Iverson and Deery (1997) found that routinization, role conflict, promotion opportunities, and a negative work atmosphere all affected job satisfaction. Mobility possibilities and dynamics of the current job have also been significantly related to subjective career success (Hui, 1988;Iverson & Deery, 1997;Kuijpers, Schyns, & Scheerens, 2006). Therefore variables measured in the current study have been broadened to include contextual or environmental factors that influence culinary success.…”
Section: Motivational Skillsmentioning
confidence: 99%